1994
DOI: 10.1002/jnr.490390511
|View full text |Cite
|
Sign up to set email alerts
|

Dopamine and serotonin turnover rate in the retina of rabbit, rat, goldfish, and Eugerres plumieri: Light effects in goldfish and rat

Abstract: The concentration of dopamine, and its metabolites 3,4-dihydroxyphenylacetic and homovanillic acids, as well as serotonin and its metabolite 5-hydroxyindoleacetic acid, were determined in the retina of two teleosts, C. auratus (goldfish) and E. plumieri (mojarra), and two mammals, R. norvegicus (rat) and O. cuniculus (rabbit). The turnover rate of these monoamines were investigated in the four species by the calculation of the ratio monoamine/metabolite as an indirect index, and in goldfish and rat by the inhi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
3
0

Year Published

1996
1996
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 64 publications
1
3
0
Order By: Relevance
“…In conclusion, we found that DA and 5-HT directly modulate homomeric GABAρ1 receptors but not GABA A receptors. Since the concentrations of DA and 5-HT in the retina vary between 0.9 and 470 μM and 0.1 and 590 μM, , respectively, both of which are within the range of modulation we found for GABAρ1, it is plausible that these interactions occur in the retina. Such possibilities will be explored in future studies.…”
Section: Resultssupporting
confidence: 66%
“…In conclusion, we found that DA and 5-HT directly modulate homomeric GABAρ1 receptors but not GABA A receptors. Since the concentrations of DA and 5-HT in the retina vary between 0.9 and 470 μM and 0.1 and 590 μM, , respectively, both of which are within the range of modulation we found for GABAρ1, it is plausible that these interactions occur in the retina. Such possibilities will be explored in future studies.…”
Section: Resultssupporting
confidence: 66%
“…Hence, we can not conclude whether 5-HT acts as a melatonin precursor in the retina and/or whether it modulates retinal function. Notably, in goldfish (Carassius auratus) and mojarra (Eugerres plumieri) 5-HT metabolism changes with photoperiod and can be blocked by p-chlorophenylalanine (PCPA), a Tph activity blocker (Lima and Urbina, 1994). Among mammals retinal 5-HT levels are low and it seems to be accumulated in some cells rather than being synthesized (Osborne and Barnett, 1990).…”
Section: Pineal and Retinamentioning
confidence: 99%
“…However, although the enzymatic pathway has now been identified in the rat retina, the major question of the origin(s) of 5-HT, as precursor of melatonin, is still unresolved. 5-HT can neither be consistently detected within the retina of adult rat (Lima and Urbina 1994), nor can its presence be demonstrated using immunohistochemical techniques (Tornqvist et al 1983), whereas N-acetyl serotonin, which is the product of AANAT, the substrate of HIOMT and precursor of melatonin, has been detected (Pang et al 1981).…”
mentioning
confidence: 97%
“…However, a weak signal has been obtained for TPH mRNAs (Besançon et al 1997). TPH activity does seem to occur as the TPH inhibitor p-chlorophenylalanine decreases 5-HT concentration (Lima and Urbina 1994). In contrast, aromatic L-amino acid decarboxylase (AADC; EC 4.1.1.28), the enzyme that decarboxylates 5-hydroxytryptophan (5-HTP) to 5-HT has been localized within rat photoreceptor cells (Nguyen-Legros et al 1994).…”
mentioning
confidence: 99%